The "Good Enough Mother": Winnicott to Neuroscience, to the culture and context-specific perspectives of Johannesburg Inner City Mothers - Mojanaga, Kelebogile Lesego (My University, 2020)
Mothering is a role that holds cultural meaning and significance, much of which is not universal. This paper presents a model of a ‘good enough mother’ as conceptualized by seven mothers living and working or studying in the inner city of Johannesburg. This is then compared and contrasted with Winnicott’s (1960) model of the ‘good enough’ mother, and characteristics of parenting currently endorsed by neuroscience research. The convergences, divergences and context-specific nuances in mothering that emerged between models are presented. While all models converge around the concepts of maternal availability, maternal protection, and the need to foster resilience in children, the study found that factors such as access to resources, social support, occupation, and the participants’ perceptions of culturally prescribed expectations of mothers influence these mothers’ experiences, understandings and performance of mothering.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Clinical Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2019